(untitled) (The Hague, 2000)
Commercial agency, distribution and franchising agreements form the backbone of cross-border commercial activity, and international lawyers are frequently confronted with issues relating to such agreements. This authoritative, practical reference work describes the law of the European Union relating to commercial agency, distribution and franchising, together with a detailed comparative analysis of the legislation and case law of the 15 Member States, Switzerland and Norway
Keywords: Commercial agents,Distributors (Commerce),Franchises (Retail trade),Thương mại,Phân phối thương mại,Quyền kinh doanh; Legal status, laws, etc.,Law and legislation,Luật và Pháp chế; European Union countries,European Union countries,European countries,Liên minh Châu Âu,Liên minh Châu Âu